Administrative and legal means of ensuring the legality of entrepreneurial activity in Ukraine - V. M. Vasyliev (Law and Safety)
The article is devoted to the study of administrative and legal means of ensuring the legality of entrepreneurial activity in Ukraine, their functional purpose in the updated conditions of modern development of the economic sphere of the state and the financial level of society’s life. In accordance with the stated scientific goal, the author analyzed the current state of administrative and legal means of state support of entrepreneurship in Ukraine; described the existing accounting and legalizing regimes as types of administrative-legal regime, which concern the official registration of individuals and legal entities, as subjects of economic activity, and the regulation of regulatory requirements for the conduct of entrepreneurial activity. The author’s vision on the content of the concept “legality (legitimacy) of entrepreneurial activity in Ukraine” is formulated, based on current trends in the development of relations in the field of entrepreneurship and the objective need for their regulation by administrative and legal norms.The further developed the provision according to which, under the lawfulness (lawfulness) of entrepreneurial activity in Ukraine, it is proposed to understand the legalization (granting of legal force) of entrepreneurial activity, carried out by the duly registered economic entities, that is, the actual receipt of the last right to engage in entrepreneurial activity in the procedure established, based on the constitutionally enshrined right of everyone to implement such a kind of economic activity, as well as general principles management, defined in аrt. 6 of the Commercial Code of Ukraine. It has been established that the lawful nature of entrepreneurial activity ensures the protection of the life, health and property of each individual member of society, environmental protection and the environment, and the economic and national security of the state.